Decision Points - Bush, George W. (London Virgin Books, 2010)
A memoir of George W Bush, America's 43rd president. It offers a journey through the defining decisions of his life. It describes his flaws and mistakes, as well as his accomplishments reforming education, treating HIV/AIDS in Africa, and safeguarding the country amid chilling warnings of additional terrorist attacks.
Include Colur Illustrations and Index
Keywords: Bush, George W. -- (George Walker), -- 1946- -- Presidents -- United States -- Biography. -- United States -- Politics and government -- 2001-2009.